Age-related Changes in the Fracture Resistance of Male Fischer F344 Rat Bone - Uppuganti, Sasidhar (Bone, 2015)
In addition to the loss in bone volume that occurs with age, there is a decline in material properties. To test new therapies or diagnostic tools that target such properties as material strength and toughness, a pre-clinical model of aging would be useful in which changes in bone are similar to those that occur with aging in humans. Toward that end, we hypothesized that similar to human bone, the estimated toughness and material strength of cortical bone at the apparent-level decreases with age in the male Fischer F344 rat. In addition, we tested whether the known decline in trabecular architecture in rats translated to an age-related decrease in vertebra (VB) strength and whether non-X-ray techniques could quantify tissue changes at micron and sub-micron length scales. Bones were harvested from 6-, 12-, and 24-month (mo.) old rats (n=12 per age). Despite a loss in trabecular bone with age, VB compressive strength was similar among the age groups. Similarly, whole-bone strength (peak force) in bending was maintained (femur) or increased (radius) with aging. There was though an age-related decrease in post-yield toughness (radius) and bending strength (femur). The ability to resist crack initiation was actually higher for the 12-mo. and 24-mo. than for 6-mo. rats (notch femur), but the estimated work to propagate the crack was less for the aged bone. For the femur diaphysis region, porosity increased while bound water decreased with age. For the radius diaphysis, there was an age-related increase in non-enzymatic and mature enzymatic collagen crosslinks. Both Raman spectroscopy and reference point indentation detected differences in tissue properties with age, though the trends did not necessarily match observations from human tissue.